Nursing engagement in research priorities focused on health systems and services in Latin America countries - Tonda L. Hughes; Maureen George; Ruby Shah; Bruna Moreno Dias; Jennifer E. Dohrn; Silvia Helena De Bortoli Cassiani (BMC, 2022)
Abstract Background A strong nursing research agenda in Latin America is fundamental to universal health coverage. Nursing science can make important contributions to the health of Latin American people through knowledge generation that directly informs nursing practice, professional education, and health policy. Methods We used a cross-sectional survey design to assess nursing involvement in health systems and services research in Latin America in five priority areas: Policies and education related to nursing human resources; Structure, organization and dynamics of health systems and services; Science, technology, innovation, and information systems in public health; Health policies, governance, and social control; and Social studies in the health field. Results Nursing and midwifery participants (N = 856) from Latin American countries completed the survey. Respondents who reported conducting research focused primarily on Policies and Education related to Nursing Human Resources and Structure, Organization, and Dynamics of Health Systems and Services. Across the five priority areas, more nurses reported using research findings and/or being aware of research than conducting research. Conclusions Survey results indicate that nursing research in Latin America is currently disproportionately focused on nursing education and practice. More research focused on information technology, nurse's impact on public health, and the threats posed by nurse migration is needed to better address health needs of Latin American populations.